Disclosure bias - Fischer, Paul E.; Verrecchia, Robert E. (Journal of Accounting and Economics, 2004)
We suggest that transparent bias in management disclosures may result from managers processing information in a heuristic, as distinct from Bayesian, fashion when they face imperfect or head-to-head competition. We predict that transparent bias in disclosures is positively related to the extent of head-to-head competition. In addition, when disclosure is discretionary, we show that managers who exhibit viable, heuristic behavior are less likely to disclose than managers who exhibit Bayesian behavior. Finally, when disclosure is discretionary, we show that the increase in the proportion of uninformed managers who exhibit viable, heuristic behavior encourages more disclosure by an informed manager.